Congenital giant Bednar tumor in a child: surgical challenges in a young infant: a case report - Vidhya Gunasekaran; Nitin J. Peters; Ram Samujh (SpringerOpen, 2020)
Abstract Background Bednar tumor is a pigmented variant of the uncommon dermatofibrosarcoma protuberans (DFSP). It is a disease of the middle aged and elderly and has been rarely described in the pediatric population. Case presentation We report a rare case of a giant Bednar tumor present since birth, in a 2-year-old male child. It was present over the lower back and managed by surgical excision. Conclusions Bednar tumor is a rarity in children and is managed with aggressive wide local excision with margin of at least 1 cm. A close clinical follow-up is mandatory.